# lim n n 1 0 converges lim n n n 2 ln 2 2 15

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: π/3 ≈ 1.047 +1 +∞ (b) +∞ e−u du = √ π/2 ≈ 0.8862 0 4 +∞ 2 2 e−ax dx = √ a √ 2 2σ du, √ 2πσ e−x dx ≈ 0.8862; 0 61. (a) +∞ a dx, 2 0 e (b) √ 66. −2 = √ 2 + π/2 0 1 sin(1 − u2 )du = 2 1 1 sin(1 − u2 )du ≈ 1.187 0 Chapter 9 Supplementary Exercises 336 CHAPTER 9 SUPPLEMENTARY EXERCISES 1. (a) (c) (e) (g) (i) integration by parts, u = x, dv = sin x dx reduction formula u-substitution: u = x3 + 1 integration by parts: dv = dx, u = tan−1 x u-substitution: u = 4 − x2 (b) (d) (f ) (h) u-substitution: u = sin x u-substitution: u = tan x u-substitution: u = x + 1 trigonometric substitution: x = 2 sin θ 1 3 1 9 2. (a) x = 3 tan θ (d) x = 3 sec θ (b) x = 3 sin θ √ (e) x = 3 tan θ (c) x = (f ) x = 5. (a) #40 (d) #108 (b) #57 (e) #52 (c) #113 (f ) #71 6. (a) u = x2 , dv = √ 1 0 √ x x2 + 1 dx, du = 2x dx, v = 3 x dx = x2 x2 + 1 = √ x2 + 1 1 0 sin θ tan θ √ x2 + 1; 1 −2 x(x2 + 1)1/2 dx 0 2 2 − (x2 + 1)3/2 3 1 = 0 √ √ 2√ 2 − [2 2 − 1] = (2 − 2)/3 3 (b) u2 = x2 + 1, x2 = u2 − 1, 2x dx = 2u du, x dx = u du; 1 0 x3 √ dx = x2 + 1 1 0 x2 √ x dx = x2 + 1 √ 2 1 u2 − 1 u du u √ 2 13 u −u 3 (u − 1)du = 2 = 1 √ 2 = (2 − 1 7. (a) u = 2x, sin4 2x dx = 1 2 sin4 u du = 1 1 3 − sin3 u cos u + 2 4 4 sin2 u du 1 1 3 1 − sin u cos u + = − sin3 u cos u + 8 8 2 2 du 3 3 1 sin u cos u + u + C = − sin3 u cos u − 8 16 16 3 3 1 sin 2x cos 2x + x + C = − sin3 2x cos 2x − 8 16 8 (b) u = x2 , x cos4 (x2 )dx = 1 2 cos4 u du = 11 3 cos3 u sin u + 24 4 cos2 u du = 1 31 1 cos3 u sin u + cos u sin u + 8 82 2 = 3 3 1 cos3 u sin u + cos u sin u + u + C 8 16 16 = 1 3 3 cos3 (x2 ) sin(x2 ) + cos(x2 ) sin(x2 ) + x2 + C 8 16 16 8. (a) With x = sec θ: 1 dx = x3 − x cot θ dθ = ln | sin θ| + C = ln du √ x2 − 1 + C ; valid for |x| &gt; 1. |x| √ 2)/3 337 Chapter 9 (b) With x = sin θ: 1 dx = − x3 − x 1 dθ = − sin θ cos θ 2 csc 2θ dθ √ = − ln | csc 2θ − cot 2θ| + C = ln | cot θ| + C = ln 1 − x2 + C, 0 &lt; |x| &lt; 1. |x| (c) By partial fractions: − 1/2 1/2 1 + + x x+1 x−1 dx = − ln |x| + = ln 1 1 ln |x + 1| + ln |x − 1| + C 2 2 |x2 − 1| + C ; valid for all x except x = 0, ±1. |x| √ 9. (a) With u = x: √ 1 1 dx = 2 √ du = 2 sin−1 (u/ 2) + C = 2 sin−1 ( x/2) + C ; √√ x 2−x 2 − u2 √ with u = 2 − x: √ √ √ 1 1 dx = −2 √ du = −2 sin−1 (u/ 2) + C = −2 sin−1 ( 2 − x/ 2) + C ; √√ 2 x 2−x 2−u completing the square: 1 dx = sin−1 (x − 1) + C . 1 − (x − 1)2 (b) In the three results in part (a) the antiderivatives diﬀer by a constant, in particular √ √ 2 sin−1 ( x/2) = π − 2 sin−1 ( 2 − x/ 2) = π/2 + sin−1 (x − 1). 2 10. A = 1 A B 3−x C 3−x = + 2+ ; A = −4, B = 3, C = 4 dx, 2 3 + x2 x x (x + 1) x x x+1 A = −4 ln |x| − 3 + 4 ln |x + 1| x 2 1 3 3 3 3 = (−4 ln 2 − + 4 ln 3) − (−4 ln 1 − 3 + 4 ln 2) = − 8 ln 2 + 4 ln 3 = + 4 ln 2 2 2 4 11. Solve y = 1/(1 + x2 ) for x getting 1−y and integrate with respect to y x= 1 to y to get A = 0 +∞ 12. A = e +∞ but lim e +∞ 0 = 1/e e →+∞ − y = 1 / (1 + x2) x xe−x dx = 2π lim −e−x (x + 1) 0 →+∞ 1 1−y dy (see ﬁgure) y ln x ln x − 1 dx = lim − →+∞ x2 x 13. V = 2π 14. y ( + 1) = lim →+∞ = 2π lim 0 →+∞ 1 − e− ( + 1) +1 1 = lim = 0 so V = 2π →+∞ e e dx 1 tan−1 (x/a) = lim →+∞ a x2 + a2 = lim 0 →+∞ π 1 tan−1 ( /a) = = 1, a = π/2 a 2a Chapter 9 Supplementary Exercises 338 2 u1/2 du = − cos3/2 θ + C 3 15. u = cos θ, − 16. Use Endpaper Formula (31) to get 17. u = tan(x2 ), 1 2 1 1 1 tan6 θ − tan4 θ + tan2 θ + ln | cos θ| + C . 6 4 2 tan7 θdθ = 1 tan3 (x2 ) + C 6 u2 du = √ √ 18. x = (1/ 2) sin θ, dx = (1/ 2) cos θ dθ, 1 √ 2 1 cos3 θ sin θ 4 π /2 1 cos4 θ dθ = √ 2 −π/2 3 =√ 42 19. x = √ 3 tan θ, dx = 1 1 dθ = sec θ 3 1 3 π /2 1 cos θ sin θ 2 π /2 + −π/2 + −π/2 x+3 21. (x + 1)2 + 1 cos θ dθ = cos2 θ dθ −π/2 π /2 dθ −π/2 3π 31 = √ π= √ 4 22 82 1 x sin θ + C = √ +C 3 3 3 + x2 √ 1 1 du = √ tan−1 [(sin θ − 3)/ 3] + C u2 + 3 3 dx, let u = x + 1, u+2 √ du = u2 + 1 = 1 2 π /2 √ 3 sec2 θ dθ, cos θ dθ, let u = sin θ − 3, (sin θ − 3)2 + 3 20. 3 4 u(u2 + 1)−1/2 + √ 2 u2 +1 du = u2 + 1 + 2 sinh−1 u + C x2 + 2x + 2 + 2 sinh−1 (x + 1) + C Alternate solution: let x + 1 = tan θ, (tan θ + 2) sec θ dθ = = 22. Let x = tan θ to get sec θ tan θ dθ + 2 sec θ dθ = sec θ + 2 ln | sec θ + tan θ| + C x2 + 2x + 2 + 2 ln( x2 + 2x + 2 + x + 1) + C. x3 1 dx. − x2 A B C 1 = + 2+ ; A = −1, B = −1, C = 1 so x2 (x − 1) x x x−1 1 dx − x − = 23. 1 dx + x2 1 1 dx = − ln |x| + + ln |x − 1| + C x−1 x x−1 tan θ − 1 1 + ln + C = cot θ + ln + C = cot θ + ln |1 − cot θ| + C x x tan θ A B C 1 1 1 1 = + + ;A=− ,B= ,C= so (x − 1)(x + 2)(x − 3) x−1 x+2 x−3 6 15 10 − 1 6 1 1 dx + x−1 15 1 1 dx + x+2 10 1 dx x−3 1 1 1 ln |x + 2| + ln |x − 3| + C = − ln |x − 1| + 6 15 10 339 24. Chapter 9 A Bx + C 1 = +2 ; A = 1, B = C = −1 so + x + 1)...
View Full Document

Ask a homework question - tutors are online